Nekateri sociološki vidiki problematike žensk v znanosti med delom in družino v slovenski družbi - Goriup, Jana; Oblak, Urška (Revija za elementarno izobraževanje, 2011)
Some Sociological Aspects of Women in Science Being Divided between Work and Family in Slovene Society. In present-day society the image of a woman is still linked to prejudice that restricts women and steals their motivation for quality work performance. Especially because the environment is of opinion there are certain activities that a woman is incapable of doing or unable to do them good enough. Science is one of the spheres where - for the level of education and the quantity of work - this holds true. Our aim was to research and study the position of women in science and in family environment in contemporary Slovene society. We focused largely on their present position which is still denoted by discrimination and inequality. All these fields are extremely important in light of society not losing the intellectual potential of women. Within the framework of this thesis, a research was made which determined the position of women in science in our country. On the other hand, we have to consider the fact that in comparison with the past, women are nowadays allowed new roles and possibilities of public activity, but only providing they carry out their traditional functions. That is why we can assert that women in science are sexually discriminated.